Poéticas do dilaceramento e da desolação: Bernardo Carvalho e Sergio Chejfec - Paulo César Thomaz (Estudos de Literatura Brasileira Contemporânea, 2010)
This work consists of an analysis of how the Brazilian and Argentine contemporary narrative, specifically the romances Teatro (1998) by the Brazilian writer, Bernardo Carvalho, and Los incompletos (2004) of the Argentine Sergio Chejfec, fictionalize different poetics of the contemporary experience, with emphasis mainly on impossibility and impediments to transform the lived moment in narrative material.